Angiogenesis and Collagen Type IV Expression in Different Endothelial Cell Culture Systems. (4th April 2013) - Bahramsoltani, M.; Slosarek, I.; De, W.; Plendl, J.
Summary In vitro angiogenesis assays constitute an important tool for studying the mechanisms of angiogenesis and for identification of pro‐ and anti‐angiogenic substances. Therefore, endothelial cell and media systems used for in vitro angiogenesis assays are required to mimic the angiogenic process in vivo including endothelial capability to express collagen type IV as a component of the basement membrane. In this study, the expression of collagen type IV and its α chains (α1‐6) was investigated in different endothelial cell culture systems in vitro qualitatively and quantitatively. These systems included four different batches of microvascular endothelial cells derived from the human skin, heart and lung, from which only two batches were found to be angiogenic and two batches were classified as non‐angiogenic. Distribution of the transcripts of the α chains of collagen type IV was similar in all cell and media systems investigated. However, secretion and deposition of a stable extracellular network of collagen type IV could only be observed in the angiogenic cultures. In conclusion, the consecutive steps of the angiogenic cascade in vivo as well as in vitro depend on an increasing secretion and subsequent extracellular deposition of collagen type IV.